HUBUNGAN PENGETAHUAN DENGAN KEBERSIHAN GIGI DAN MULUT SISWA KELAS VII DI SPMN 3 SELEMADEG TIMUR TABANAN TAHUN 2018 - Asep Arifin Senjaya; Kadek ADI Tresna Yasa (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2019)
Oral health status is also influenced by the interaction of four factors, namely behavior, environment, health services, and genetics. Developing countries like Indonesia, behavior is the most dominant factor in influencing the oral health status. Health behavior is divided into three, namely knowledge, attitudes, and actions. Knowledge is a very important domain for the formation of one's actions. Dental and oral health care is often ignored by adolescents. Conclusions Kadek Adi Tresna Yasa's research results, namely the level of knowledge about dental and oral hygiene of Grade VII students of Middle N 3 Selemadeg Timur Tabanan Regency 2018 sufficient criteria. While dental and oral hygiene with moderate criteria. The purpose of this study was to determine the relationship between knowledge about dental and oral hygiene with dental and oral hygiene of Grade VII students of SMPN 3 Selemadeg Timur Tabanan Regency in 2018. This type of cross sectional study, uses secondary data from Kadek Adi Tresna Yasa's research. Spearmen correlation test results obtained sig .: 0.717. Conclusion there is no relationship between knowledge about dental and mouth hygiene with dental and mouth hygiene of Grade VII students of SMPN 3 Selemadeg Timur Tabanan Regency in 2018